An Analysis of Students’ Grammatical Error in Impromptu Speaking - Umahdi, Kissisina; Kholid, M. Ridho (Raden Intan State Islamic University of Lampung, Indonesia, 2025)
Grammar is a fundamental aspect of the English language. However, many students continue to make grammatical errors, particularly in speaking. One of the most effective methods for analyzing students' grammatical errors in speaking is through impromptu speech. This study aimed to analyze the types of grammatical errors in students' impromptu speaking and identify the causes of these errors. The research employed a descriptive-qualitative method. The population consisted of fourth-semester English Education students at UIN Raden Intan Lampung, with a sample of 20 students selected through purposive sampling. Data collection involved observing and recording students' impromptu speaking. The recordings were analyzed to identify grammatical errors based on Carl James' classification, which includes morphological and syntactical errors. This study specifically focused on errors related to tense. Additionally, a focus group interview was conducted to determine the causes of these errors using Norrish's framework, which categorizes causes into carelessness, first language interference, and translation. The findings revealed that 19 out of 20 students made grammatical errors related to tense. The errors were classified into morphological and syntactical errors. In terms of morphology, 101 verb morphology errors were identified. In syntax, 33 clause errors were found. The most frequent tense-related errors involved incorrect forms of the simple present and past tense. Furthermore, the interview results indicated that students' grammatical errors were primarily caused by carelessness, first language interference, and translation